2018
DOI: 10.1088/0256-307x/35/8/087303
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Two-Dimensional Quantum Spin Hall Effect in Triangular Transition-Metal Carbides

Abstract: Though the quantum spin Hall effect (QSHE) in two-dimensional (2D) crystals has been widely explored, the experimental realization of quantum transport properties is only limited to HgTe/CdTe or InAs/GaSb quantum wells. Here we employ a tight-binding model on the basis of 𝑑 𝑧 2 , 𝑑π‘₯𝑦, and 𝑑 π‘₯ 2 βˆ’π‘¦ 2 orbitals to propose QSHE in the triangular lattice, which are driven by a crossing of electronic bands at the Ξ“ point. Remarkably, 2D oxidized Mxenes W2M2C3 are ideal materials with nontrivial gap of 0.12 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…15,16 Recently, theoretical predictions have identified diverse MXene monolayers as potential 2D TIs, with their surfaces primarily terminated by oxygen (O) and fluorine (F) groups. 17–27 However, due to the relativistic effect, 2D MXene TIs with a large spin–orbit coupling (SOC) effect have mostly been limited to materials with heavy elements. In other words, the dependency on elements is still indispensable for increasing the nontrivial bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recently, theoretical predictions have identified diverse MXene monolayers as potential 2D TIs, with their surfaces primarily terminated by oxygen (O) and fluorine (F) groups. 17–27 However, due to the relativistic effect, 2D MXene TIs with a large spin–orbit coupling (SOC) effect have mostly been limited to materials with heavy elements. In other words, the dependency on elements is still indispensable for increasing the nontrivial bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…29–31 The QSH effect has also been theoretically predicted in mono-transition metal MXenes 32,33 and ordered double transition metal MXenes. 34–38 Most theoretical studies have shown that the bandgaps of 2D MXene TIs are generally observed in heavy elements due to their large spin–orbit coupling (SOC) effect. Thus, the most common methods of tuning the bandgaps in MXenes are to change the heavy elements.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2D transition metal car-bides/carbonitrides (denoted as MXenes) have attracted significant attention as electrode materials. [10][11][12][13][14][15] MXene can be prepared from the early ternary transition metal carbides, nitrides, or carbonitrides (MAX) by means of the etching approaches, where M is an early transition metal (M = Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W), A is mainly a group IIIA or IVA element (A = Al, Si, Ga, Ge, In, Sn), X is C or/and N, and n = 1, 2 or 3. [16] In the exfoliation process, the A atoms are replaced by T -terminations (T = F, O or OH), leading to functionalized MXene.…”
Section: Introductionmentioning
confidence: 99%